Os institutos federais : reflexões sobre a ifetização a partir do processo de elaboração do regimento geral do IFS - Barbosa, Ana Cecília Campos (2012)
The text covers a discussion of the most recent reform in the field of professional education in Brazil, ifetização. The creation of the Institutos Federais de Educação, Ciência e Tecnologia was the reorganization of federal integration CEFETs, Agrotécnicas, Escolas Técnicas and universities units linked to the same region, a process that resulted in the appearance of 38 institutes. We use some concepts of Institutional Analysis as a theoretical as well as a set of documents and literature, in order to develop a historical overview to compose our analyzes. The study aims to expose a reflective work about the institutionalization of the Instituto Federal de Educação, Ciência e Tecnologia, observing the ifetização process in our state through the elaboration of the General Rules of the Instituto Federal de Sergipe, when it was in the process at the time of elaboration of this study. Themes were discussed teacher training, special programs, community participation, integration and autonomy. At the end, we concluded that despite being a model that proposes a break with past practices and reforms, many aspects and historical trends repeat themselves in the process of institutionalization of the Institute.